Cerium stabilized zirconia beads and preparation process thereof
Through the combination of liquid phase chemical co-precipitation method and modified polyethylene glycol dispersant, the problem of uneven mixing of nanoparticles in colored zirconia ceramics is solved, and the uniform color, stability and high strength of cerium-stable zirconia beads are achieved.
Patent Information
- Application Number
- CN202510085051.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-20
AI Technical Summary
In the prior art, when preparing colored zirconia ceramics, it is difficult to achieve uniform mixing of nanoparticles, resulting in the color of the final product being not uniform and stable enough.
The liquid phase chemical co-precipitation method is used to uniformly wrap the colorant on the surface of cerium stabilized zirconia, and modify polyethylene glycol as a dispersant to improve the dispersion of the powder in water and prevent nanoparticles from agglomerating.
The cerium-stable zirconia beads have achieved better color uniformity and stability, higher strength, and avoided the problem of colorant volatility during high-temperature sintering.
Smart Images

Figure NPN9C2ONA0GQZSZB9JXHYC9BPEW1HMHALMRWW3CG 
Figure RDFQ8TFTPZPYZTDPEZUF2K6IOAYCRYQP4EVNHYHN
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramics, and in particular to a cerium-stabilized zirconia bead and a preparation process thereof. Background Art
[0002] Zirconia beads have high density and can generate greater impact force during grinding, effectively improving grinding efficiency. They have excellent strength and toughness, can withstand greater pressure and friction, have stable performance during grinding, and reduce material contamination caused by bead breakage. They also have excellent wear resistance and are one of the most widely used grinding media. In terms of application areas, in the ceramic industry, they are used for wet grinding of ceramic raw materials to improve the fineness and uniformity of raw materials and improve the quality of ceramic products. In the magnetic material industry, they can effectively grind and disperse magnetic material powders to achieve the required particle size and performance requirements. In the coating and ink industry, they can grind pigments and fillers to improve the fineness and gloss of coatings and inks, and are used in the production of products such as high-grade automotive paints, mobile phone paints, and inkjet inks. In the pharmaceutical and food industry, due to its good chemical stability and biocompatibility, it is used to grind and disperse raw materials to ensure product quality and safety.
[0003] The characteristics of zirconia beads have an important impact on their applications in different industrial fields. Its high density allows it to have greater inertia and impact force during the grinding process, which can more effectively crush and disperse materials, and improve grinding efficiency in fields such as ceramics and magnetic materials. Its high strength and toughness allow it to withstand greater pressure and impact force during grinding, and it is not easy to break. In the fields of coatings and inks, it can ensure the stability and reliability of the grinding process and improve product quality. Its excellent wear resistance reduces the amount of wear, and in the fields of medicine and food, it can ensure that no impurities are introduced during grinding, ensuring product purity and safety. Its good chemical stability enables it to remain stable in various acidic and alkaline environments, and it is widely used in chemical, electronic and other fields. In recent years, with the development and application of rare earth-colored zirconia ceramics, it has attracted much attention. The development of colored zirconia ceramics with high strength and high toughness has important theoretical significance and market application prospects.
[0004] CN112778798A relates to the field of ceramic technology, and describes in detail a black ceramic colorant, a black zirconium oxide ceramic powder, a black zirconium oxide ceramic and a production method thereof. The black ceramic colorant is mainly composed of a composite doping material Ti1-xy (AxBy) Oz, wherein A can be at least one of Mg, Ca, Sr, Zn, La, Sm, Bi, and In, and B can be at least one of Ta, Sn, Nb, and Fe, and the molar ratio of x to y is between 0.001 and 0.15 and 0.001 and 0.2, respectively. In addition, the colorant can also contain a colorant, which can be one of oxides containing chromium, tungsten, and molybdenum, and the molar ratio of Ti to the metal element in the colorant is 20 to 99 to 1. The black zirconium oxide ceramic powder is mainly composed of 75 to 97 parts of yttrium stabilized zirconium oxide and 3 to 25 parts of black ceramic colorant. By this technology, black zirconium oxide ceramics with pure, uniform and easy-to-control color can be manufactured.
[0005] CN105669191A discloses a formula of a black zirconium oxide ceramic material, including the following components by mass percentage: 0-5% iron oxide, 0-5% cobalt oxide, 0-5% chromium oxide, 0-5% aluminum oxide, 0-5% nickel oxide, 0-5% manganese oxide, 0-5% zinc oxide, 2-6% yttrium oxide, 0-5% titanium oxide, 0-5% silicon dioxide, 0-5% cerium oxide, and the rest is zirconium oxide containing hafnium oxide. The black zirconium oxide ceramic made of this material has a smaller powder particle size and good dispersibility, so it has a higher hiding power and blackness, and a lower light transmittance. The patent also discloses a black zirconium oxide ceramic prepared using this material formula and a production method thereof. At present, the main method for synthesizing colored zirconium oxide is a mechanical mixing method, which is simple in process and easy to realize industrial production. However, it has some limitations, such as the inability to completely eliminate the agglomeration of nanoparticles, and it is difficult to achieve uniform mixing of the coloring phase and the matrix nanoparticles, which may result in the color of the final product being not uniform and stable enough. Although black zirconia ceramics can be produced through a molding and sintering process, the products obtained by this method have poor color stability because the colorant is easily volatilized during the high-temperature sintering process. At the same time, this method may also cause some environmental problems. Summary of the invention
[0006] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to provide cerium-stabilized zirconia beads with uniform color, better stability and higher strength and a preparation process thereof.
[0007] The preparation method of colored zirconia ceramics mainly varies due to the different coloring processes. Commonly used ceramic coloring methods include: solid phase mixing method, liquid phase infiltration method, chemical coprecipitation method and chemical coating method. The colored ceramics are sintered at high temperature to obtain colored zirconia ceramics. However, the biggest disadvantage of the solid phase is that the agglomeration between nanoparticles during the ball milling process is difficult to overcome, and the zirconia nanoparticles and the colorant are not mixed evenly, thus affecting the coloring effect of the colorant in the ceramic. The present invention adopts a liquid phase method to uniformly coat the colorant on the surface of cerium-stabilized zirconia by chemical coprecipitation, and obtains black cerium-stabilized zirconia after high-temperature sintering. The present invention uses modified polyethylene glycol as a dispersant, which not only does not cause agglomeration between cerium-stabilized zirconia nanoparticles, but also greatly improves the dispersibility of the powder in water. This is because the modified polyethylene glycol not only has good water solubility, but also the grafted hydroxyl groups after modification can undergo ligand exchange with oxides, so that it can be well adsorbed on the surface of cerium-stabilized zirconia. After the long chains of the polyethylene glycol itself are dispersed in water, not only the water solubility can be improved, but also the agglomeration of the nanoparticles can be prevented through steric hindrance. Therefore, the nanoparticles and the colorant are mixed more evenly, so that the finally obtained zirconia beads have uniform color, and the zirconia beads have better stability and higher strength.
[0008] Pure zirconia undergoes phase transformation during cooling from high temperature to room temperature, from cubic phase (c) to tetragonal phase (t) and then to monoclinic phase (m). The t to m phase transformation occurs at about 1150°C, accompanied by a volume expansion of about 5%. This volume expansion may cause the material to crack easily during sintering, while cerium oxide can form a solid solution with zirconia, which can hinder the phase transformation process (from cubic phase to tetragonal phase to monoclinic phase) of zirconia when it is cooled from high temperature to room temperature, thereby improving the structural stability of the material. Cerium oxide stabilizer is conducive to obtaining metastable tetragonal zirconia in a wider composition range, providing excellent conditions for phase transformation toughening of zirconia. When the material is loaded, the stress induces a phase transformation from tetragonal phase to monoclinic phase, and a large amount of fracture energy is absorbed due to the volume effect caused by the phase transformation, so that the material exhibits abnormally high fracture toughness. The addition of cerium oxide can increase the thermal stability of zirconia materials, which is particularly important for the application of materials in high temperature environments.
[0009] To achieve the above object, the present invention provides a preparation process of cerium-stabilized zirconia beads, comprising the following steps:
[0010] S1. Add zirconium oxide and cerium oxide into water and grind to a slurry particle size of D 50 <0.5μm, after adding a binder, spray granulation is performed to obtain cerium-stabilized zirconia powder;
[0011] S2. Add cerium-stabilized zirconia powder and modified polyethylene glycol into water, and after ultrasonic dispersion for 1-2 hours, add an aqueous solution containing ferric nitrate and aluminum nitrate, mix well, and then add ammonia water to adjust the pH to alkaline. Continue stirring for 2-3 hours, filter, wash with water, and dry. The powder is formed into a green body, and the green body is sintered and polished to obtain cerium-stabilized zirconia beads.
[0012] The amounts of the raw materials used are as follows, in parts by weight: 85-88 parts of zirconium oxide, 9-13 parts of cerium oxide, 0.5-5 parts of modified polyethylene glycol, 1-2 parts of a binder, and 40-100 parts of water.
[0013] Furthermore, the adhesive is polyvinyl alcohol.
[0014] The preparation method of the modified polyethylene glycol comprises the following steps:
[0015] Polyethylene glycol monomethyl ether, a modifier and a catalyst are placed in a medium, heated and stirred under an inert atmosphere, and the solvent is removed after the reaction is completed to obtain modified polyethylene glycol.
[0016] Furthermore, the mass ratio of the polyethylene glycol monomethyl ether to the modifier and the catalyst is 5-10:1:0.01-0.1.
[0017] Furthermore, the catalyst is an aqueous solution of sulfuric acid.
[0018] Furthermore, the temperature range of the heating and stirring is 130-140°C.
[0019] Furthermore, the preparation method of the modified polyethylene glycol comprises the following steps:
[0020] Add polyethylene glycol monomethyl ether, a modifier and a sulfuric acid aqueous solution into water, wherein the mass ratio of the polyethylene glycol monomethyl ether to the modifier and the sulfuric acid aqueous solution is 5-10:1:0.01-0.1, heat to 130-140° C. and stir for 4-6 hours under an inert atmosphere, and remove the solvent after the reaction is completed to obtain modified polyethylene glycol.
[0021] Preferably, the modifier is one of p-hydroxybenzoic acid, gallic acid or 2,3,4,5,6-pentahydroxybenzoic acid.
[0022] Furthermore, the rotation speed of the atomizer of the granulation tower of the spray granulation is 9000-10000 r / min, the inlet temperature is 200-250°C, and the outlet temperature is 100-120°C.
[0023] Furthermore, the sintering temperature is 1400-1500°C.
[0024] Furthermore, the aqueous solution of ferric nitrate is 0.2 mol / L, and the aqueous solution of aluminum nitrate is 0.1 mol / L.
[0025] Furthermore, the mass ratio of the iron nitrate and aluminum nitrate to zirconium oxide is 0.01-0.03:0.01-0.02:85-88.
[0026] Furthermore, the pH value is adjusted to be in the range of 9 to 10.
[0027] Beneficial effects of the present invention:
[0028] The present invention uses modified polyethylene glycol as a dispersant, which not only does not cause agglomeration between cerium-stabilized zirconia nanoparticles, but also greatly improves the dispersibility of the powder in water. This is because the modified polyethylene glycol not only has good water solubility, but also the grafted hydroxyl groups after modification can undergo ligand exchange with oxides, so that it can be well adsorbed on the surface of cerium-stabilized zirconia. After the long chains of the polyethylene glycol itself are dispersed in water, not only the water solubility can be improved, but also the agglomeration of the nanoparticles can be prevented through steric hindrance. Therefore, the nanoparticles and the colorant are mixed more evenly, so that the finally obtained zirconia beads have uniform color, and the zirconia beads have better stability and higher strength. DETAILED DESCRIPTION
[0029] 2,3,4,5,6-pentahydroxybenzoic Acid, CAS: 145279-23-8.
[0030] Polyethylene glycol monomethyl ether, Mw = 400 g / mol, Haian Petrochemical Plant, Jiangsu Province.
[0031] Sulfuric acid aqueous solution, 6 mol / L.
[0032] Ammonia water, 25wt%.
[0033] Polyvinyl alcohol, model: PVA-2488, Langfang Feitai New Material Technology Co., Ltd.
[0034] Polyethylene glycol, model: PEG400, Dow Chemical.
[0035] Example 1
[0036] A process for preparing cerium-stabilized zirconia beads comprises the following steps, measured in parts by weight:
[0037] S1. Add 86 parts of zirconium oxide and 11 parts of cerium oxide to 40 parts of water and grind to a slurry particle size of D. 50 <0.5μm; after adding 1.5 parts of polyvinyl alcohol, spray granulation was performed to obtain cerium-stabilized zirconia powder, the granulation tower atomizer speed was 9500r / min, the inlet temperature was 220℃, and the outlet temperature was 110℃;
[0038] S2. Add cerium-stabilized zirconia powder and 3 parts of modified polyethylene glycol to 50 parts of water, and after ultrasonic dispersion for 1 hour, add 0.2 mol / L ferric nitrate aqueous solution and 0.1 mol / L aluminum nitrate aqueous solution, the mass ratio of ferric nitrate and aluminum nitrate to zirconium oxide is 0.02:0.015:86. After mixing evenly, add ammonia water to adjust the pH to 9.5. Continue stirring for 3 hours and then filter. Wash with water and then dry. The powder is molded to obtain a green body. The green body is sintered at 1450°C for 2 hours and then polished to obtain cerium-stabilized zirconia beads.
[0039] The preparation method of the modified polyethylene glycol comprises the following steps, measured in parts by weight:
[0040] 8 parts of polyethylene glycol monomethyl ether, 1 part of p-hydroxybenzoic acid and 0.01 parts of sulfuric acid aqueous solution were added to 100 parts of water, heated to 135° C. and stirred for 5 hours under a nitrogen atmosphere. After the reaction was completed, the solvent was removed to obtain modified polyethylene glycol.
[0041] Example 2
[0042] It is basically the same as Example 1, the only difference being that p-hydroxybenzoic acid is replaced by gallic acid.
[0043] Example 3
[0044] The process is substantially the same as Example 1, except that p-hydroxybenzoic acid is replaced by 2,3,4,5,6-pentahydroxybenzoic acid.
[0045] Comparative Example 1
[0046] A process for preparing cerium-stabilized zirconia beads comprises the following steps, measured in parts by weight:
[0047] S1. Add 86 parts of zirconium oxide and 11 parts of cerium oxide to 40 parts of water and grind to a slurry particle size of D. 50 <0.5μm, add 1.5 parts of polyvinyl alcohol and spray granulate to obtain cerium-stabilized zirconia powder, the granulation tower atomizer speed is 9500r / min, the inlet temperature is 220℃, and the outlet temperature is 110℃;
[0048] S2. Add cerium-stabilized zirconia powder and 3 parts of polyethylene glycol to 50 parts of water, and after ultrasonic dispersion for 1 hour, add 0.2 mol / L ferric nitrate and 0.1 mol / L aluminum nitrate aqueous solution, the mass ratio of ferric nitrate and aluminum nitrate to zirconium oxide is 0.02:0.015:86. After mixing evenly, add ammonia water to adjust the pH to 9.5. Continue stirring for 3 hours and then filter. Wash with water and then dry. The powder is molded to obtain a green body. The green body is sintered at 1450°C for 2 hours and then polished to obtain cerium-stabilized zirconia beads.
[0049] Comparative Example 2
[0050] A process for preparing cerium-stabilized zirconia beads comprises the following steps, measured in parts by weight:
[0051] S1. Add 86 parts of zirconium oxide and 11 parts of cerium oxide to 40 parts of water and grind to a slurry particle size of D. 50 <0.5μm, add 1.5 parts of polyvinyl alcohol and spray granulate cerium-stabilized zirconia powder, the granulation tower atomizer speed is 9500r / min, the inlet temperature is 220℃, and the outlet temperature is 110℃;
[0052] S2. Add cerium-stabilized zirconia powder to 50 parts of water, and after ultrasonic dispersion for 1 hour, add 0.2 mol / L ferric nitrate aqueous solution and 0.1 mol / L aluminum nitrate aqueous solution, the mass ratio of ferric nitrate and aluminum nitrate to zirconium oxide is 0.02:0.015:86. After mixing evenly, add ammonia water to adjust the pH to 9.5. Continue stirring for 3 hours and then filter. Wash with water and then dry. The powder is molded to obtain a green body. The green body is sintered at 1450°C for 2 hours and then polished to obtain cerium-stabilized zirconia beads.
[0053] Test Example 1
[0054] The transmittance and optical density of the cerium-stabilized zirconia beads prepared in the example and the comparative example were tested at a wavelength of 550 nm. The specific results are shown in Table 1.
[0055] Table 1 Cerium stabilized zirconia beads transmittance and optical density test results
[0056]
[0057] The transmittance at a wavelength of 550nm represents the degree of permeability of a material to light of a specific wavelength. Transmittance refers to the proportion of light transmitted by a material to the incident light, usually expressed as a percentage. At a wavelength of 550nm, this parameter is particularly important because 550nm is the average wavelength of visible light and the wavelength to which the human eye is most sensitive. Therefore, the transmittance at a wavelength of 550nm can reflect the material's ability to transmit the light to which the human eye is most sensitive, which is very important for evaluating the transparency of the material. OD value is the abbreviation of optical density, which indicates the light density absorbed by the object being tested and is a special term in the detection method. Optical density is a dimensionless value used to describe the degree of obstruction of a material to light, that is, the degree of attenuation of the intensity of light after passing through a certain material. The two can reflect the blackness of the zirconia beads, thereby reflecting the uniformity and consistency of the color.
[0058] As can be seen from Table 1, the transmittance of the cerium-stabilized zirconia beads in the embodiment is significantly lower than that in the control example, while the OD value is higher than that in the control example, which indicates that the cerium-stabilized zirconia beads in the embodiment have a higher blackness and better uniformity of black, so the transmittance of light is lower and the optical density is higher. In the embodiment, the modified polyethylene glycol is used as a dispersant, which not only does not cause agglomeration between the cerium-stabilized zirconia nanoparticles, but also greatly improves the dispersibility of the powder in water. This is because the modified polyethylene glycol not only has good water solubility, but also the grafted hydroxyl groups after modification can undergo ligand exchange with the oxide, so it can be well adsorbed on the surface of the cerium-stabilized zirconia. The long chain of the polyethylene glycol itself can not only improve the water solubility after being dispersed in water, but also prevent the agglomeration of the nanoparticles through steric hindrance. Therefore, the nanoparticles are more evenly mixed with the colorant, so that the final zirconia beads have uniform color and better blackness. Compared with Examples 1 to 2, Example 3 has more phenolic hydroxyl groups in 2,3,4,5,6-pentahydroxybenzoic acid, so it has better ligand exchange ability with oxides, so the modified polyethylene glycol has better adsorption ability for zirconium oxide, so the cerium-stabilized zirconia beads and the colorant are mixed more uniformly, resulting in a better final coloring effect.
[0059] Test Example 2
[0060] The cerium-stabilized zirconia beads prepared in the examples and control examples were tested for flexural strength and Vickers hardness. The flexural strength test was conducted in accordance with GB / T4741-1999 Test Method for Flexural Strength of Ceramic Materials. The specific test results are shown in Table 2.
[0061] Table 2 Flexural strength and Vickers hardness test results of cerium-stabilized zirconia beads
[0062]
[0063] Flexural strength refers to the maximum bearing capacity of a material under bending load, that is, the maximum bending moment it can withstand without breaking. For cerium-stabilized zirconia beads, high flexural strength means that they can withstand large forces without breaking easily, which is very important for grinding media because it needs to remain intact in high-pressure and high-abrasion environments.
[0064] Vickers hardness is a measure of a material's hardness, reflecting its ability to resist being pressed in by foreign objects. The high Vickers hardness of cerium-stabilized zirconia beads means they can more effectively crush or grind materials during the grinding process while keeping their own wear rate low.
[0065] As can be seen from Table 2, the hardness and strength of the cerium-stabilized zirconia beads prepared in the embodiment and the control example are both good. This may be because cerium oxide can form a solid solution with zirconia. This solid solution can hinder the phase change process (from cubic phase to tetragonal phase and then to monoclinic phase) that occurs when zirconia is cooled from high temperature to room temperature, thereby improving the structural stability of the material. The cerium oxide stabilizer is conducive to obtaining metastable tetragonal zirconia in a wider range of components, providing excellent conditions for the phase change toughening of zirconia. When the material is loaded, the stress induces a phase change from tetragonal phase to monoclinic phase, and a large amount of fracture energy is absorbed due to the volume effect generated by the phase change, so that the material exhibits higher strength. Compared with the control example, the embodiment has higher strength. This may be because the modified polyethylene glycol used as a dispersant in the embodiment not only does not cause agglomeration between cerium-stabilized zirconia nanoparticles, but also greatly improves the dispersibility of the powder, so the obtained zirconia beads have a more stable structure. Compared with other embodiments, Example 3 has more phenolic hydroxyl groups, so it has better ligand exchange ability with oxides. Therefore, the modified polyethylene glycol has better adsorption ability for zirconium oxide, and the cerium-stabilized zirconia beads are mixed with the colorant more uniformly, which may lead to uniformity in the structure, thereby having a positive impact on stability.
[0066] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for preparing cerium-stabilized zirconia beads, characterized in that: The steps include: S1. Add zirconium oxide and cerium oxide into water, grind until the slurry particle size D50 is less than 0.5 μm, add a binder and perform spray granulation to obtain cerium-stabilized zirconium oxide powder; S2. Add cerium-stabilized zirconia powder and modified polyethylene glycol to water, disperse them by ultrasonic for 1-2 hours, add an aqueous solution containing iron nitrate and aluminum nitrate, mix well, add ammonia water to adjust the pH to alkaline, continue stirring for 2-3 hours, filter, wash with water and dry, shape the powder to obtain a green body, sinter and polish the green body to obtain cerium-stabilized zirconia beads; The amounts of the raw materials are as follows, by weight: 85-88 parts of zirconium oxide, 9-13 parts of cerium oxide, 0.5-5 parts of modified polyethylene glycol, 1-2 parts of adhesive, and 40-100 parts of water; The preparation method of the modified polyethylene glycol comprises the following steps: Polyethylene glycol monomethyl ether, a modifier and a catalyst are placed in a medium, heated and stirred under an inert atmosphere, and after the reaction is completed, the solvent is removed to obtain modified polyethylene glycol; The modifier is one of p-hydroxybenzoic acid, gallic acid or 2,3,4,5,6-pentahydroxybenzoic acid.
2. The method for preparing cerium-stabilized zirconia beads according to claim 1, characterized in that: The adhesive is polyvinyl alcohol.
3. The method for preparing cerium-stabilized zirconia beads according to claim 1, characterized in that: The mass ratio of the polyethylene glycol monomethyl ether to the modifier and the catalyst is 5-10:1:0.01-0.
1.
4. The method for preparing cerium-stabilized zirconia beads according to claim 1, characterized in that: The catalyst is an aqueous solution of sulfuric acid.
5. The method for preparing cerium-stabilized zirconia beads according to claim 1, characterized in that: The temperature range of the heating and stirring is 130-140°C.
6. The method for preparing cerium-stabilized zirconia beads according to claim 1, characterized in that: The atomizer speed of the granulation tower of the spray granulation is 9000-10000 r / min, the inlet temperature is 200-250°C, and the outlet temperature is 100-120°C.
7. The method for preparing cerium-stabilized zirconia beads according to claim 1, characterized in that: The sintering temperature is 1400-1500°C.
8. The method for preparing cerium-stabilized zirconia beads according to claim 1, characterized in that: The aqueous solution of ferric nitrate has a concentration of 0.2 mol / L, and the aqueous solution of aluminum nitrate has a concentration of 0.1 mol / L.
9. The method for preparing cerium-stabilized zirconia beads according to claim 1, characterized in that: The mass ratio of the iron nitrate and aluminum nitrate to zirconium oxide is 0.01-0.03:0.01-0.02:85-88.
10. A cerium-stabilized zirconia bead, characterized in that: Prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Black zirconia ceramic and preparation method thereof
CN105669191A
Black ceramic pigment, black zirconia ceramic powder, black zirconia ceramic and preparation method thereof
CN112778798A
Polyethylene glycol-modified halloysite carbon nanotubes and preparation method thereof
CN102702799A
Method for removing SOx in gas by using modified polyethylene glycol
CN103432890A